PENGARUH PANDEMI COVID-19 PADA RELEVANSI NILAI INFORMASI AKUNTANSI (STUDI PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA) - Aryo Bimo Setya Permana; Tuah Panjaitan; Rafiqah Humaira (BONANZA : Jurnal Ilmiah Ekonomi, Bisnis dan Keuangan, 2023)
Value relevance is the ability to explain (explanatory power) accounting information as a basis for investors as users of financial statements in making decisions. However, the Covid-19 pandemic has become a challenge for stock market players. The company conducts business options for the continuity of operations during the pandemic. This research aims to see the influence of the COVID-19 pandemic on the relevance of the value of accounting information to the LQ45 sample on the Indonesia Stock Exchange, namely 45 companies with high market capitalization. The method used uses the Ohlson model as a basis for testing by taking adjusted R2. The results found that the relevance of the book equity value during the pandemic rose because investors were more concerned with book value than profit information. Hence, the relevance of the importance of earnings fell. This research is limited to using only book value and profit variables with the Ohlson model; future research can use other accounting elements by modifying the model.